Dry-method solid electrolyte membrane, preparation method thereof and battery
By using PTFE and PAA as binders in dry solid electrolyte membranes and using process steps such as high-speed shear and high-pressure differential rolling, the problems of insufficient thermal stability and ionic conductivity of the existing electrolyte membrane are solved, and higher mechanical and electrical properties are achieved, and the safety and energy density of the battery are improved.
Patent Information
- Application Number
- CN202510036549.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-18
AI Technical Summary
The existing dry solid electrolyte membrane has poor thermal stability and low ionic conductivity in high-temperature environments, which limits its application in high-energy-density batteries.
Polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA) are used as binders, and dry process combined with high-speed shearing and high-pressure differential roller pressing and other steps were prepared to produce a dry solid electrolyte membrane with good adhesion effect and tensile strength.
It improves the mechanical and electrical properties of the electrolyte membrane, enhances the binding force with solid electrolyte materials and inorganic fillers, promotes the construction of an ion transmission network, and improves the safety performance and energy density of the battery.
Smart Images

Figure BDA0005235698780000081 
Figure HDA0005235698790000011 
Figure HDA0005235698790000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of dry process and secondary battery technology, in particular to a dry solid electrolyte membrane and a preparation method thereof, and a battery comprising the dry solid electrolyte membrane. Background Art
[0002] Lithium / sodium ion batteries have occupied an important position in the field of energy storage due to their advantages such as long life and high energy density, and have been widely used in fields such as electronic products and electric vehicles. However, traditional liquid electrolytes have safety hazards and performance limitations, which restrict their application in large-scale equipment. Therefore, it is particularly important to study solid electrolytes with high energy density and high safety. Dry solid electrolyte membranes have become an important direction for the development of solid-state battery technology due to their advantages such as environmental protection, economic benefits and simplified production process.
[0003] At present, the binder used in most dry solid electrolyte membranes is polyvinylidene fluoride (PVDF). PVDF is widely used as a binder material in batteries due to its good chemical stability and high mechanical strength. PVDF can form good adhesion with active materials and conductive agents to ensure the structural stability of the electrode. However, the defect of PVDF is that its thermal stability is poor, especially easy to degrade in high temperature environment, thus affecting the overall performance of the battery. In addition, the ionic conductivity of PVDF is relatively low, which limits its application in high energy density batteries.
[0004] Polytetrafluoroethylene (PTFE) is the best binder choice for dry solid electrolyte membranes due to its high voltage stability, good mechanical properties and corrosion resistance. However, PTFE is electrochemically unstable in the negative electrode environment and easily accepts electrons, which may lead to side reactions and reduce the battery capacity. In addition, PTFE has limited lithium ion conductivity, and due to its limited viscoelasticity, it cannot ensure sufficient interfacial adhesion between the active material, solid electrolyte, and conductive carbon, which may lead to the formation of voids during the volume expansion / contraction of the active material, reducing the battery capacity and cycle stability.
[0005] Therefore, developing a solid-state electrolyte membrane system suitable for dry process and synergistically improving its mechanical properties (adhesion, mechanical strength, etc.) and electrical properties (conductivity, thermal safety, etc.) is of great significance to the development of solid-state battery technology. Summary of the invention
[0006] In view of the above-mentioned problems in the prior art, the present invention provides a dry solid electrolyte membrane, which can be prepared by a dry process and has good adhesion effect and tensile strength, as well as good resistivity index, which is beneficial to the performance of battery electrical performance.
[0007] The present invention first provides a dry solid electrolyte membrane, the raw materials of which, by weight, include 30%-38% solid electrolyte material, 1%-3% inorganic filler and 60%-67% binder, wherein the binder is polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA) in a mass ratio of (95-99):(1-5).
[0008] In some embodiments, the solid electrolyte material in the present invention is an inorganic solid electrolyte material, including one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
[0009] In some embodiments, the inorganic filler in the present invention is selected from inorganic ceramic oxide materials, including one or more of MgO (magnesium oxide), Al2O3 (aluminum oxide), SiO2 (silicon dioxide), zeolite, and montmorillonite.
[0010] In a second aspect, the present invention further provides a method for preparing the above-mentioned dry solid electrolyte membrane, comprising the following steps:
[0011] S1: mixing the solid electrolyte material, the inorganic filler and the binder by dry mixing to obtain a premixed material;
[0012] S2: subjecting the premixed material to high-speed shearing at 60-70°C and a high-speed shearing speed of 12000-14000 r / min to fiberize the binder; the specific surface area of the material after high-speed shearing reaches 15%-30% of the specific surface area of the premixed material;
[0013] S3: preforming the fiberized material to obtain a preformed solid electrolyte membrane;
[0014] S4: performing high-pressure differential-speed rolling on the preformed solid electrolyte membrane, wherein the high-pressure pressure is 20-30T and the differential speed ratio is 1:1.4-1:1.6;
[0015] S5: Finally, roll pressing is performed, the rolling pressure is 8-12T, the rolling temperature is 95-105°C, and the rolling reduction ratio is 15%-20%, to obtain a dry solid electrolyte membrane product.
[0016] In some embodiments, the stirring time of the dry mixing in step S1 is 20-30 min, and the stirring speed is 850-950 r / min.
[0017] In some embodiments, the high-speed shear stirring time of step S2 is 15-20 minutes.
[0018] In some embodiments, the rolling speed of the rollers in step S5 is 4-6 m / min.
[0019] In a third aspect, the present invention also provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned dry solid-state electrolyte membrane.
[0020] In some embodiments, the solid-state battery is a lithium-ion battery or a sodium-ion battery, and the corresponding positive electrode active material adopts a lithium battery positive electrode active material or a sodium battery positive electrode active material, preferably a lithium battery positive electrode active material; the lithium battery positive electrode active material is selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium titanate, etc.; the sodium battery positive electrode active material is selected from transition metal oxides such as O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyanion compounds such as sodium vanadium phosphate (Na3V2(PO4)3), Prussian blue compounds such as Fe4[Fe(CN)6]3.
[0021] In some embodiments, the negative electrode active material of the solid-state battery can be one or more of silicon-based materials, carbon materials, and lithium titanate. The silicon-based materials include porous silicon or porous silicon carbon, and the carbon materials include hard carbon, soft carbon, or graphite.
[0022] In some embodiments, the positive electrode sheet or negative electrode sheet of the solid-state battery also includes a conductive agent, a binder, and a solid electrolyte. These materials are not limited. As some optional examples, the conductive agent can be selected from one or more of carbon nanotubes, Super P, Ketjen black, carbon fiber or acetylene black, the binder can be selected from one or more of fluorine-containing polymers, such as polyvinylidene fluoride-hexafluoropropylene copolymer, PTFE and PVDF-HFP, and the solid electrolyte can be selected from one or more of inorganic solid electrolytes or polymer solid electrolytes. Among them, the binder and solid electrolyte in the positive electrode sheet or negative electrode sheet can be the same or different from the system material used in the dry solid electrolyte membrane of the present invention.
[0023] Compared with the prior art, the present invention has at least the following beneficial effects:
[0024] The present invention successfully prepared a dry solid electrolyte membrane with excellent comprehensive performance by innovatively combining polyacrylic acid (PAA) and polytetrafluoroethylene (PTFE) as binders. PTFE, as the main binder, retains its excellent mechanical properties and pressure resistance. The addition of PAA provides additional carboxyl groups and softening properties, enhances the bonding force with solid electrolyte materials and inorganic fillers, and promotes the coating of the binder on the surface of the material and the formation of similar beneficial interface films.
[0025] The present invention also optimizes the preparation conditions of the dry process, and through high-speed shearing, high-pressure differential rolling and other steps, further improves the fiberization requirements of PTFE as the main body, and constructs a more sufficient ion transmission network. This process not only reduces the operational difficulty of one-step fiberization, but also improves the stability of the fiberization state. By accurately controlling parameters such as specific surface area change, pressure, differential speed and temperature, the electrolyte membrane of the present invention achieves optimal performance in ion conductivity, mechanical strength and interface stability, effectively improving the safety performance and energy density of the battery, and providing important technical support for the development of solid-state battery technology.
[0026] The dry solid electrolyte membrane obtained by the present invention has the following indicators: tensile strength>1.0MPa, flatness controlled within ±3, electronic resistivity>3.6*10 4 Ω*cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a surface SEM image of the dry solid electrolyte membrane prepared in Example 1 of the present invention.
[0029] Figure 2 The charge and discharge curves of the battery assembled in Example 2 of the present invention at room temperature 25°C and a current density of 0.5C. DETAILED DESCRIPTION
[0030] Detailed preparation methods and technical steps are provided in the embodiments of the present invention, and are intended to fully illustrate the specific implementation process of the present invention. However, these detailed technical details only represent a specific way to realize the present invention, and are not intended to limit the core content of the present invention or its protection scope. It should be understood by those skilled in the art that these embodiments are only for illustrative purposes and should not be regarded as limiting the only or exclusive implementation mode of the present invention.
[0031] In the first aspect, the present invention first provides a dry solid electrolyte membrane, the raw materials of which, by weight, include 30%-38% solid electrolyte material, 1%-3% inorganic filler and 60%-67% binder, and the binder is polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA) in a mass ratio of (95-99):(1-5).
[0032] The present invention overcomes the shortcomings of PTFE in the dry process and its disadvantages in electrical properties by combining a small amount of PAA and PTFE as a binder into the solid electrolyte membrane preparation system, and combines solid electrolyte materials and inorganic fillers to build an efficient ion transport network, successfully obtaining a dry solid electrolyte membrane with excellent comprehensive performance.
[0033] Using PTFE as the main binder retains its good mechanical properties and pressure resistance. Its excellent fiberization ability is the key to the successful implementation of the dry process, providing good binding ability and thermal safety at a higher ratio of solid electrolyte materials and inorganic fillers. PAA provides more carboxyl groups and has stronger softening properties, which is conducive to synergizing PTFE to enhance the binding force between the solid electrolyte material and the inorganic filler, and is conducive to promoting the formation of a coating layer similar to an interface film on the surface of the solid electrolyte material and the inorganic filler. However, the amount of PAA added must be strictly controlled to avoid a significant reduction in mechanical strength, and to regulate the degree of decomposition of PTFE on the interface film and the amount of fluoride formed. While the binder provides a good fiberized cross-linked structure, the solid electrolyte material ensures ion conductivity and mechanical strength. The combination of a limited amount of inorganic fillers is conducive to regulating the ion transport behavior in the electrolyte bulk phase, producing a uniform ion flux, inhibiting lithium dendrites, and improving the interface channel and stability. It is an important supplement to the fiberized cross-linked structure of the combined compound binder in the dry process to form a stable transmission network.
[0034] In a second aspect, the present invention further provides a method for preparing the above-mentioned dry solid electrolyte membrane, comprising the following steps:
[0035] S1: mixing the solid electrolyte material, the inorganic filler and the binder by dry mixing to obtain a premixed material;
[0036] S2: subjecting the premixed material to high-speed shearing at 60-70°C and a high-speed shearing speed of 12000-14000 r / min to fiberize the binder; the specific surface area of the material after high-speed shearing reaches 15%-30% of the specific surface area of the premixed material;
[0037] S3: preforming the fiberized material to obtain a preformed solid electrolyte membrane;
[0038] S4: performing high-pressure differential-speed rolling on the preformed solid electrolyte membrane, wherein the high-pressure pressure is 20-30T and the differential speed ratio is 1:1.4-1:1.6, so that the preformed solid electrolyte membrane is further fully fiberized;
[0039] S5: Finally, roll pressing is performed, the rolling pressure is 8-12T, the rolling temperature is 95-105°C, and the rolling reduction ratio is 15%-20%, to obtain a dry solid electrolyte membrane product.
[0040] The present invention further optimizes and controls the preparation conditions in the dry process, explores a set of preparation process conditions for the dry solid electrolyte membrane that is particularly suitable for the above-mentioned system of the present invention, and ensures the effective improvement of performance indicators. The strong mechanical ability of PTFE and the higher solid electrolyte material and inorganic filler filling further improve the fiberization requirements of the binder. Therefore, in the preparation process, on the one hand, the combination of high-speed shear fiberization and high-pressure differential rolling further fiberization makes the construction of the ion transmission network connected by PAA and PTFE cross-linking more sufficient, and on the other hand, the conditional regulation of the two steps reduces the difficulty of the one-step fiberization operation process, and provides a suitable relaxation time for fiberization to reach a full state, so that the fiberization state can be more stable. The control of the change in specific surface area of high-speed shear, the pressure and differential control of high-pressure differential rolling, and the temperature pressure and thinning amount control of the roller rolling all enable the dry solid electrolyte membrane composition system of the present invention to obtain a good intermediate state, thereby achieving the optimal performance indicators of the dry solid electrolyte membrane product.
[0041] As some examples, the solid electrolyte material in the present invention is an inorganic solid electrolyte material, including oxide solid electrolytes, sulfide solid electrolytes and halide solid electrolytes. The present invention prefers oxide solid electrolytes, and further includes perovskite-type solid electrolytes such as LLTO (lithium lanthanum titanium oxide), garnet-type solid electrolytes such as LLZO (lithium lanthanum zirconium oxide), and NASICON-type solid electrolytes such as LATP (lithium aluminum titanium phosphate).
[0042] As some examples, the inorganic filler in the present invention is selected from inorganic ceramic oxide materials, including but not limited to MgO (magnesium oxide), Al2O3 (aluminum oxide), SiO2 (silicon dioxide), zeolite, montmorillonite, etc.
[0043] As some examples, the conditions for dry mixing and stirring in step S1 are generally not limited, but the optimized conditions are conducive to improving the high-speed shearing efficiency and shortening the fibrillation time of high-speed shearing, so the stirring time can be controlled at 20-30 minutes and the stirring speed can be controlled at 850-950r / min.
[0044] As some examples, the high-speed shear stirring time of step S2 is 15-20 minutes.
[0045] As some examples, the high-pressure differential rolling in step S4 not only further provides fiberization, but the differential design also promotes the rearrangement of the cross-linked network of particles and binders, and adjusts the internal network structure while also affecting the surface flatness and thinning amount. The double-roll rolling in step S5 is a necessary supplement to the high-pressure differential rolling, which is beneficial to the adjustment of the film structure of the high-pressure differential rolling at low pressure and high temperature. The appropriate double-roll rolling rate is beneficial to improving the film quality and surface flatness. The optimized double-roll rolling rate can be 4-6m / min.
[0046] The present invention also provides a solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and the above-mentioned dry solid electrolyte membrane. The material system of the positive electrode sheet and the negative electrode sheet is not limited, and any system known in the prior art that is suitable for solid-state batteries can be used.
[0047] The following is an explanation of the specific implementation cases.
[0048] Example 1
[0049] (1) Preparation of dry solid electrolyte membrane
[0050] Step 1: Mixing. Weigh 30% LATP powder, 66.32% PTFE powder, 0.68% PAA powder, and 3% Al2O3 powder in a container according to the mass ratio, and stir and mix them evenly in a mixer. Parameter setting: speed 900r / min, time 30min.
[0051] Step 2: Shearing and fiberization. Take out the mixed materials and put them into a high-speed mixer, and stir and shear them at high speed to make them fiberized. Parameter settings: speed 12000r / min, time 20min, temperature 65℃. The specific surface area of the obtained fiberized powder material is between 15% and 30% of the specific surface area of the material before fiberization.
[0052] Step 3: Preforming. The fiberized material is rolled on a roller mill. First, the material is rolled into a thin sheet at an appropriate roll gap.
[0053] Step 4: High-pressure differential roller pressing: The preformed sheet is further fully fiberized during the film-forming process at a pressure of 25T and a differential speed ratio of 1:1.5.
[0054] Step 5: Roller pressing: The roller pressing is set at a pressure of 10T, a rolling speed of 5m / min, a rolling temperature of 100°C, and a thinning ratio of 15% to obtain a dry solid electrolyte membrane with uniform thickness.
[0055] (2) Positive electrode production
[0056] Step 1: Mixing: Weigh 2500g of lithium nickel cobalt manganese oxide, 48.4g of binder, 115.7g of conductive agent, and 67.3g of LATP powder in a container, and add appropriate amount of NMP to mix.
[0057] Step 2: Coating.
[0058] Step 3: Rolling.
[0059] Step 4: Production.
[0060] (3) Negative electrode production
[0061] Weigh 2000g of silicon carbon, 79.3g of binder, 42.9g of conductive agent, and 21.4g of LATP powder in a container, add appropriate amount of deionized water and mix. The process is the same as the positive electrode production process.
[0062] (4) Assemble the above-mentioned dry solid electrolyte membrane, positive electrode sheet and negative electrode sheet into a battery.
[0063] Example 2
[0064] The dry solid electrolyte membrane and battery were prepared by the same method as in Example 1, except that the shear fiberization stirring time was changed to 15 min, and the rolling reduction ratio was changed to 20%.
[0065] Example 3
[0066] The dry solid electrolyte membrane and battery were prepared by the same method as in Example 1, except that the binder ratio was changed to PTFE:PAA=98:2, and the high-pressure differential roller differential ratio was changed to 1:1.6.
[0067] Comparative Example 1
[0068] The dry solid electrolyte membrane and battery were prepared by the same method as in Example 1, except that the differential speed ratio of the high-pressure differential roller was changed to 1:1.1.
[0069] Comparative Example 2
[0070] The dry solid electrolyte membrane and battery were prepared by the same method as in Example 1, except that the rotation speed of the shear fiberization was changed to 10000 r / min.
[0071] Comparative Example 3
[0072] The dry solid electrolyte membrane and battery were prepared by the same method as in Example 1, except that the thinning ratio of the roll pressing was changed to 30%.
[0073] The performance indicators of the above embodiments and comparative examples of the present invention were tested, and the results are listed in Tables 1 and Figure 1-2 middle.
[0074] Table 1
[0075]
[0076] From the test results, it can be seen that by adjusting the optimized dry process conditions of the present invention, the system of the present invention is used to prepare a dry solid electrolyte membrane, and the obtained product has synergistically improved comprehensive performance indicators in terms of tensile strength, flatness and resistivity. Figure 1 It shows that the solid electrolyte membrane is evenly dispersed, has a dense structure, and no agglomerates are formed. Figure 2 It is demonstrated that the solid electrolyte membrane of the present invention has stable capacity development and good electrochemical stability.
[0077] It can be seen from Comparative Examples 1-3 that the optimization effect of process parameters under non-optimized conditions on performance is reduced, and inappropriate process control makes it difficult to promote the full fiberization of PTFE+PAA and is not conducive to the good construction of an ion conductive network, resulting in deficiencies in both mechanical and electrical properties.
[0078] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A dry solid electrolyte membrane, wherein the raw materials thereof, by weight, include 30%-38% solid electrolyte material, 1%-3% inorganic filler and 60%-67% binder, wherein the binder is polytetrafluoroethylene and polyacrylic acid in a weight ratio of (95-99):(1-5).
2. The dry solid electrolyte membrane according to claim 1, characterized in that: The solid electrolyte material is an inorganic solid electrolyte material, including one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
3. The dry solid electrolyte membrane according to claim 1, characterized in that: The inorganic filler is selected from inorganic ceramic oxide materials, including one or more of MgO (magnesium oxide), Al2O3 (aluminum oxide), SiO2 (silicon dioxide), zeolite, and montmorillonite.
4. The method for preparing the dry solid electrolyte membrane according to any one of claims 1 to 3, comprising the following steps: S1: mixing the solid electrolyte material, the inorganic filler and the binder by dry mixing to obtain a premixed material; S2: subjecting the premixed material to high-speed shearing at 60-70°C and a high-speed shearing speed of 12000-14000 r / min to fiberize the binder; the specific surface area of the material after high-speed shearing reaches 15%-30% of the specific surface area of the premixed material; S3: preforming the fiberized material to obtain a preformed solid electrolyte membrane; S4: performing high-pressure differential-speed rolling on the preformed solid electrolyte membrane, wherein the high-pressure pressure is 20-30T and the differential speed ratio is 1:1.4-1:1.6; S5: Finally, roll pressing is performed, the rolling pressure is 8-12T, the rolling temperature is 95-105°C, and the rolling reduction ratio is 15%-20%, to obtain a dry solid electrolyte membrane product.
5. The method for preparing a dry solid electrolyte membrane according to claim 4, characterized in that: The stirring time of the dry mixing in step S1 is 20-30 min, and the stirring speed is 850-950 r / min.
6. The method for preparing a dry solid electrolyte membrane according to claim 4, characterized in that: The high-speed shear stirring time of step S2 is 15-20 minutes.
7. The method for preparing a dry solid electrolyte membrane according to claim 4, characterized in that: The rolling speed of the rollers in step S5 is 4-6 m / min.
8. A solid-state battery comprising a positive electrode sheet, a negative electrode sheet and a dry solid electrolyte membrane prepared by the method according to any one of claims 4 to 7.
9. The solid-state battery according to claim 8, characterized in that: Solid-state batteries are either lithium-ion batteries or sodium-ion batteries.
10. The solid-state battery according to claim 9, characterized in that: The positive electrode active material of the solid-state battery adopts the positive electrode active material of the lithium battery or the positive electrode active material of the sodium battery; The positive electrode active material of the lithium battery is selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium titanate, etc.; The positive electrode active material of the sodium battery is selected from transition metal oxides such as O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyanion compounds such as sodium vanadium phosphate (Na3V2(PO4)3), Prussian blue compounds such as Fe4[Fe(CN)6]3; The negative electrode active material of the solid-state battery adopts one or more of silicon-based materials, carbon materials, and lithium titanate; the silicon-based material includes porous silicon or porous silicon carbon, and the carbon material includes hard carbon, soft carbon, or graphite. The positive electrode or negative electrode of the solid-state battery also includes a conductive agent, a binder, and a solid electrolyte; the conductive agent is selected from one or more of carbon nanotubes, Super P, Ketjen black, carbon fiber or acetylene black, the binder is selected from one or more of fluorine-containing polymers, such as polyvinylidene fluoride-hexafluoropropylene copolymer, PTFE and PVDF-HFP, and the solid electrolyte is selected from one or more of inorganic solid electrolytes or polymer solid electrolytes.
Citation Information
Cited By
Dry electrolyte membrane and preparation method and application thereof
CN120497435A
Dry electrolyte membrane, preparation method and application thereof
CN120497435B